Influence of seed skin condition, seed drying and concentrations of coconut water on seed viability of papaya seeds (Carica papaya L.) - Parhimpunan, Anwar; Haryati; Sitepu, Ferry Ezra T. (Jurnal Online Pertanian Tropik, 2019)
Dormansi seeds was caused on the physic of seeds, embryo physiologic or a combination of those two, it is needed the seed drying and concentrations of coconut water to solved dormancy. The purpose of this research is to know the influence of seed treatment, seed drying and concentrations of coconut water on seed viability of papaya seeds, used randomized block design with three factors. The first factor is seed treatment (sarcotesta and without sarcotesta), the second factor is seed drying (2, 4 and 6 day) and the third factor is concentrations of coconut water (0, 50 and 100 %). The results showed that seeds without sarcotesta increasing seed of water doses, normal seedling percentage, vigor index, seedling fresh weight, seedling dry weight, increased the rate of germination and reducing of not growt seedling percentage. Six days of seed drying significantly affected normal seedling percentage, vigor index and reducing of not growt seedling percentage. Fifty percents of concentration of coconut water significantly affected normal seedling percentage, vigor index and reducing of not growt seedling percentage. There is significantly affected interaction between seeds without sarcotesta and six days of seed drying to the rate of germination. There is significantly affected interaction between seeds without sarcotesta and fifty percents of concentrations of coconut water to seed of water doses. There is significantly affected interaction between seeds without sarcotesta, six days of seed drying and fifty percents of concentrations of coconut water to the rate of germination.